(3GdLRGAGJ GdJi JhbYgG GdGOGQI HefGSHI GdfTGW GdGOGQi ai ZjQ eLGd GdYbhO hGdJCOjH (B: s (3OQGSI ebGQfI (B/ s - (3fGUQ MSjf eMSf GHhLeg GdYLeis; (3jSQi eMeO GdYUGQ s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2010)
(3XgQJ GdLRGAGJ GdGOGQjI GdYGeI dehGLgI GfhGY ef GdLQGFe dG JSJMb ehGLgJgG HYbhHGJ LfGFjI fXQG dJaGgJgG hbdI GgejJgG ai fXQ GdeLJeY hGfeG jcai dehGLgJgG JhbjY GdLRGAGJ GdGOGQjI GdYGeI GdJi JhbYgG GdGOGQI Ohf GdQLhY Gdi GdbVGA hPdc ai ZjQ eLGd GdYbhO GdJCOjH (B. (3hGf cGf gfGc HYV GdGYJQGVGJ GdehLgI VO gPg GdLRGAGJ hGdJi JJeKd ai JYGQVgG eY eHOC GdaUd Hjf GdSdWGJ hYOe JhGaQ GdVeGfGJ GdYbGHjI dGf GdGOGQI GdJi JhbYgG JeKd GdNUe hGdMce ai faS GdhbJs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGes
(3HHdjhLQGajG(B: (3UaMGJ (B425-443s
Keywords: (3VeGfGJ GdLRGA GdEOGQjs; (3GdLRGAGJ GdEOGQjIs; (3GdLRGAGJ GdEOGQjI GdYGeIs; (3GdLRGAGJ GdJCOjHjIs; (3Gdhba GdEOGQjs; (3GdZdb GdEOGQjs; (3GdMd GdEOGQjs; (3GdERGdI GdEOGQjIs; (3SMH GdJQGNjUs; (3YOe QLYjI GdLRGAGJ GdEOGQjIs; (3QSGFd LGeYjI s -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes